Erosion Hazard Level And Design Of Soil Conservation For Flood Mitigation In The Arui Watershed, Indonesia - Mahmud Mahmud; Mutakim Mutakim; Wahyudi Wahyudi; Febriza Dwiranti; Sri Endayani (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
Excessive surface runoff is often underestimated concerning flood mitigation. Indeed, flooding has become a recurring disaster in the past 20 years in Indonesia. This research aims to determine the erosion hazard level and develop conservation plans for dryland agriculture and oil palm plantations to mitigate surface runoff, thereby reducing the risk of flooding. The data collected includes hydrology, dryland agricultural areas, oil palm plantations, and topography, which are analyzed based on threats and conservation potential. Conservation plans that can be implemented include Minor Recharge Holes (MRH) in dryland agriculture and dead-end ponds Palm Dead Pond (PDP) in oil palm plantations. The research results indicate that the MRH design, with a diameter of 1-1.5 m and a depth of 1-1.5 m, still results in surface runoff exceeding 70%. Meanwhile, the PDP design, with a depth of 1-1.5 m and a size of 1-1.5 x 1-1.5 x 7-8 m, yields runoff below 50%, even during extreme rainfall (220 mm), with runoff being only 2%. A change in land use, primarily dominated by dryland agriculture and oil palm plantations, has been a significant factor in triggering flooding in the Arui watershed. In addition to MRH and PDP, five rivers can accommodate surface runoff, which is expected to contribute to long-term flood mitigation in the Arui watershed.